Teknis Budidaya Ikan Corydoras Venezuela (Corydoras aeneus) di Pembudidaya Ikan Hias Sukabumi, Jawa Barat - Andri Iskandar; Rini Andriani Hasibuan; Ima Kusumanti; Andri Hendriana; Imam Tri Wahyudi; Sheny Permatasari; Cecilia Eny Indriastuti; Wiyoto Wiyoto; Budi Dermawan (Faculty of Science and Technology University Ibrahimy, 2025)
The diversity of endemic fish in Indonesia has great potential to be developed into export commodities that can increase the country's foreign exchange earnings. This is supported by the increasing fish farming industry in Indonesia, both for consumption of fish and ornamental fish. In 2018, Indonesia's ornamental fish export volume increased to 257,862,207 fish, with export destinations including China, Japan, Singapore, Thailand, Taiwan, Germany, South Korea, and several other countries. Corydoras venezuela Corydoras aeneus is one of the ornamental fish species with great potential to be cultivated as an aquaculture commodity while also meeting the export market demand, in addition to being marketed domestically. Currently, the aquaculture technology for Corydoras venezuela has not been widely disseminated to the public, making the information limited to a small group of ornamental fish farmers. Therefore, studies are needed to widely distribute technical information on its cultivation so that it can serve as a reference for aquaculture business operators and ornamental fish hobbyists in managing fish farming effectively. The natural and mass spawning of Corydoras venezuela follows a sex ratio of 2 males to 1 female. The eggs of Corydoras venezuela are sticky and cling to surfaces. They typically hatch on the third day after incubation, with a success rate of around 70% to 75%. The cultivation of Corydoras venezuela occurs in two phases: the initial and secondary nursery stages. During these periods, the fry were fed natural diets such as Artemia and tubifex worms, offered freely. The study recorded an average fry survival rate of 85% to 90%. Once grown, the fish are sold, with Bandung, West Java, serving as the main market.